2016
DOI: 10.1016/j.juro.2015.11.063
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Optimize Followup Care and Reduce Hospital Readmissions after Radical Cystectomy

Abstract: Our model improves the detection of concerning symptoms after radical cystectomy by optimizing the timing and number of outpatient encounters. By understanding how to design better outpatient followup care for patients treated with radical cystectomy we can help reduce the readmission burden for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In an administrative database analysis, James et al showed that 26% of cystectomy readmissions were considered modifiable 18 and Krishnan et al demonstrated that detection of at-risk patients could be improved with early clinician contact. 21 It is likely that even in the cases of some non-modifiable readmissions, earlier identification of at-risk patients would allow for prompt intervention and a reduction in the intensity of the overall readmission episode 16 as was evident by the multiple new diagnoses present in our cohort at the time of readmission.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an administrative database analysis, James et al showed that 26% of cystectomy readmissions were considered modifiable 18 and Krishnan et al demonstrated that detection of at-risk patients could be improved with early clinician contact. 21 It is likely that even in the cases of some non-modifiable readmissions, earlier identification of at-risk patients would allow for prompt intervention and a reduction in the intensity of the overall readmission episode 16 as was evident by the multiple new diagnoses present in our cohort at the time of readmission.…”
Section: Discussionmentioning
confidence: 91%
“…Taken together, our findings demonstrate that the substantial burden of readmissions following cystectomy on patients, providers and hospital systems is not altered by whether someone has an open or robotic-assisted surgery. Therefore, efforts to reduce readmissions after cystectomy should likely focus on early communication after discharge, 20 prompt detection of clinical decompensation, and providing support during the first week after discharge, 21 rather than on the surgical approach itself.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important as interventions can be guided specifically to decrease readmissions in patients with a continent diversion. Krishnan et al modelled timing of office visits and telephone calls to prevent readmissions after RC. They showed that an office visit within 4–5 days followed by four telephone calls can maximally detect unplanned readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…With our selected cutoff of LACE ≥ 10, 24% of patients fell within the high-risk category, a group that clearly demonstrated a higher rate of postoperative issues to which a targeted intervention could be employed. Krishnan et al [17] found that optimizing the timing of follow-up calls and appointments after radical cystec-tomy allowed for identification of concerning symptoms that may lead to readmission. Using the LACE score to identify patients for hospital-based and ambulatory interventions, as well as increased postoperative follow-up would be a reasonable investigative next-step at the institutional level.…”
Section: Discussionmentioning
confidence: 99%